1990
DOI: 10.1007/bf01658524
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative and postoperative PTH secretion mode in patients with hyperparathyroidism

Abstract: The development of a sensitive 2-site immunoradiometric assay which detects only intact human PTH (1-84) enabled us to study kinetics of PTH secretion intraoperatively. In a prospective study, we assessed the PTH (1-84) secretion mode intraoperatively in 54 patients with adenomas, in 14 patients with tertiary hyperparathyroidism (HPT), and in 2 patients with persistent HPT. After the removal of adenomatous or hyperplastic tissue, a significant drop of PTH (1-84) concentration was seen. A 50% decrease in the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The intraoperative PTH assay has clearly shown a different pattern of decay in patients with an adenoma compared to those with hyperplasia [24,28,29]. Flentje et al reported that after removal of an adenoma the PTH level reached the normal range within 15 minutes, whereas following excision of the first parathyroid gland none of the patients with multiglandular disease had a PTH level within the normal range at the end of the same period of observation [29].…”
Section: Discussionmentioning
confidence: 99%
“…The intraoperative PTH assay has clearly shown a different pattern of decay in patients with an adenoma compared to those with hyperplasia [24,28,29]. Flentje et al reported that after removal of an adenoma the PTH level reached the normal range within 15 minutes, whereas following excision of the first parathyroid gland none of the patients with multiglandular disease had a PTH level within the normal range at the end of the same period of observation [29].…”
Section: Discussionmentioning
confidence: 99%
“…We considered the question of limited surgical access under local anaesthesia. In favor of this procedure were the following arguments: first, approximately 85% of patients with PHP have a single enlarged parathyroid gland [10]; second, an experienced radiologist using ultrasonography can find the adenonaa in 80% of patients [I 1]; third, intra-operative measurements of urinary cyclic AMP (UcAMP) [12][13][14][15] and intact parathyroid hormone (PTH) [16][17][18][19][20] are efficient methods to monitor the success of the operation. The aim of this study was to evaluate the results of minimal surgical therapy under local anesthesia.…”
mentioning
confidence: 99%
“…S uccessful surgical treatment of primary hyperparathyroidism is associated with a return to normal in postoperative serum intact parathyroid hormone (PTH) and serum calcium levels. It is known that the PTH concentration falls after removal of an adenoma 1–3 . Afterward, one sees a gradual recovery of the secretion by the remaining parathyroid glands, which are no longer suppressed by the adenoma 4 .…”
mentioning
confidence: 99%
“…It is known that the PTH concentration falls after removal of an adenoma. [1][2][3] Afterward, one sees a gradual recovery of the secretion by the remaining parathyroid glands, which are no longer suppressed by the adenoma. 4 In the same period, a decrease of the serum calcium is expected.…”
mentioning
confidence: 99%